2012
DOI: 10.1371/journal.pone.0039351
|View full text |Cite
|
Sign up to set email alerts
|

A Direct Comparison of Local-Global Integration in Autism and other Developmental Disorders: Implications for the Central Coherence Hypothesis

Abstract: The weak central coherence hypothesis represents one of the current explanatory models in Autism Spectrum Disorders (ASD). Several experimental paradigms based on hierarchical figures have been used to test this controversial account. We addressed this hypothesis by testing central coherence in ASD (n = 19 with intellectual disability and n = 20 without intellectual disability), Williams syndrome (WS, n = 18), matched controls with intellectual disability (n = 20) and chronological age-matched controls (n = 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
22
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 54 publications
5
22
0
Order By: Relevance
“…It will be also of a particular interest to use the present task in other clinical populations (e.g., children with Williams syndrome or in children with Down syndrome). Participants with Williams syndrome present performances indicating a central coherence processing of the material (Bernardino et al, 2012).…”
Section: Discussionmentioning
confidence: 92%
“…It will be also of a particular interest to use the present task in other clinical populations (e.g., children with Williams syndrome or in children with Down syndrome). Participants with Williams syndrome present performances indicating a central coherence processing of the material (Bernardino et al, 2012).…”
Section: Discussionmentioning
confidence: 92%
“…2 Among individuals with autism disorder, data to support the validity of the central coherence construct are somewhat mixed [3][4][5] leading some researchers to explore alternative underlying mechanisms. 6 In the ED field, data suggests that central coherence is a somewhat complex, non-unitary construct.…”
Section: Introductionmentioning
confidence: 99%
“…For example, in the current study participants were asked to view the stimuli freely but they also knew they were going to answer some question about the story at the end and thus, the specific instructions given to the participant might have impacted on their looking behaviour, thus explaining differences in the gaze strategies in the current study compared to previous studies that have measured spontaneous behaviour. In addition, there is evidence that those with ASD and WS have problems with executive functioning and difficulties with integration of information (Bernardino et al 2012;Happé and Frith 2006;Pellicano 2007;Rhodes et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Although several studies have shown evidence for a deficit to use context in WS and ASD (for a review see Bernardino et al 2012 as well as Happé and Frith 2006), studies in ASD have shown that this cannot explain performance on ToM tasks (Burnette et al 2005;Happé 1997 One reason why the current theories cannot describe the difficulties observed in ASD and WS is that they only focus on domain-specific areas of cognition to explain ToM deficits.…”
Section: Introductionmentioning
confidence: 99%